Relationship between oxidative balance score and risk of sleep-related problems - Chen, Piao; Wang, Jin; Liu, Ling; Liu, Xiaoling (Frontiers in Nutrition, 2025)
BackgroundCurrent research predominantly emphasizes the impact of diet on sleep, while overlooking the role of oxidative effects influenced by lifestyle factors. The Oxidative Balance Score (OBS) provides a comprehensive measure of individual overall oxidative stress exposure, integrating 16 dietary nutrients and 4 lifestyle factors that affect oxidative processes.MethodsTo explore the relationship between OBS and sleep-related problems, data from the National Health and Nutrition Examination Survey (NHANES) conducted between 2005 and 2008 were utilized for cross-sectional analyses. OBS was calculated following previously validated methods. Sleep-related problems were assessed based on self-reported data, including sleep duration, sleep-onset latency, obstructive sleep apnea (OSA), sleep problems and day sleepiness. Weighted logistic regression was applied to estimate OR and 95% CI. To examine potential nonlinear relationships between OBS and the risk of sleep-related problems, generalized additive models and two-part linear regression models were employed. Additionally, these models were used to identify points of inflection.ResultsLogistic regression analysis revealed an inverse association between OBS and the risk of insufficient sleep hours (OR = 0.98, 95% CI, 0.96 -0.99, p < 0.01). Generalized additive models and two-part linear regression models identified a nonlinear relationship between OBS and the risk of developing OSA and excessive sleep onset latency, with inflection points of 17.5 score and 10.5 score, respectively.ConclusionOur study showed an inverse linear relationship between OBS and the risk of insufficient sleep hours, alongside a nonlinear relationship between OBS and the risks of developing OSA and excessive sleep onset latency.